Pengaruh Kemandirian Keuangan dan Kinerja Keuangan Terhadap Keberlanjutan Keuangan (Financial Sustainability) Pada Pemerintah Kota Yogyakarta: Pengaruh Kemandirian Keuangan dan Kinerja Keuangan Terhadap Keberlanjutan Keuangan (Financial Sustainability) Pada Pemerintah Kota Yogyakarta - Miftahurrohman, Arif; Putra Prasetya, Bangun (Program Studi Manajemen, Fakultas Ekonomi, Universitas Islam Majapahit, Jawa Timur, Indonesia, 2024)
Regulations issued by the government, such as regional autonomy, mean that regional governments have the rights, authority and obligations of autonomous regions to regulate and manage government affairs and the interests of local communities themselves in the system of the Unitary State of the Republic of Indonesia. Therefore, local governments have a big responsibility in providing services to the community by paying attention to the financial conditions of local governments. Where the financial condition is good if the financial condition is sustainable. Financial sustainability is the government's ability to maintain or improve community welfare by providing public services in quantity and quality now and for the future. In order to know the condition of financial sustainability, it is very important for local governments to better understand what factors can influence the level of financial sustainability so that local governments can make good and appropriate decisions to provide services to the community in a sustainable manner. This research aims to determine the influence of financial independence and financial performance on financial sustainability (financial sustainability ratio) in the Yogyakarta City Government. The period in this research is 2013 to 2022. This research uses a quantitative approach. The research population includes the Yogyakarta City Government with an observation period from 2013 to 2022. The sample selection technique uses a purposive sampling method with the help of the SPSS version 27 program. The data analysis method used is hypothesis testing. The results of this research show that partially the Financial Independence variable has a positive and significant effect on the Financial Sustainability Ratio and the Financial Performance variable has a negative and significant effect on the Financial Sustainability Ratio. Meanwhile, simultaneously the Financial Independence variable and the Financial Performance variable have a positive and significant effect on the Financial Sustainability Ratio.